Short-Answer Questions

Question:

Short-Answer Questions

Solve: $x^{2}-(\sqrt{3}+1) x+\sqrt{3}=0$

 

Solution:

$x^{2}-(\sqrt{3}+1) x+\sqrt{3}=0$

$\Rightarrow x^{2}-\sqrt{3} x-x+\sqrt{3}=0$

$\Rightarrow x(x-\sqrt{3})-1(x-\sqrt{3})=0$

$\Rightarrow(x-\sqrt{3})(x-1)=0$

$\Rightarrow x-\sqrt{3}=0$ or $x-1=0$

$\Rightarrow x=\sqrt{3}$ or $x=1$

Hence, 1 and $\sqrt{3}$ are the roots of the given equation.

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now